Plant Growth Promotion by Volatile Organic Compounds Produced by Bacillus subtilis SYST2 - Tahir, Hafiz A. S.; Gu, Qin; Wu, Huijun; Raza, Waseem; Hanif, Alwina; Wu, Liming; Colman, Massawe V.; Gao, Xuewen (Frontiers in Microbiology, 2017)
Bacterial volatiles play a significant role in promoting plant growth by regulating the synthesis or metabolism of phytohormones. In vitro and growth chamber experiments were conducted to investigate the effect of volatile organic compounds (VOCs) produced by the plant growth promoting rhizobacterium Bacillus subtilis strain SYST2 on hormone regulation and growth promotion in tomato plants. We observed a significant increase in plant biomass under both experimental conditions; we observed an increase in photosynthesis and in the endogenous contents of gibberellin, auxin, and cytokinin, while a decrease in ethylene levels was noted. VOCs emitted by SYST2 were identified through gas chromatography-mass spectrometry analysis. Of 11 VOCs tested in glass jars containing plants in test tubes, only two, albuterol and 1,3-propanediole, were found to promote plant growth. Furthermore, tomato plants showed differential expression of genes involved in auxin (SlIAA1. SlIAA3), gibberellin (GA20ox-1), cytokinin (SlCKX1), expansin (Exp2, Exp9. Exp 18), and ethylene (ACO1) biosynthesis or metabolism in roots and leaves in response to B. subtilis SYST2 VOCs. Our findings suggest that SYST2-derived VOCs promote plant growth by triggering growth hormone activity, and provide new insights into the mechanism of plant growth promotion by bacterial VOCs.